The First and Second Law Analyses of Thermodynamics of Potato Slices Drying Process - Srivastava A.K.; Shukla S.K.; Singh U.K. (My University, 2025)
The objective of the work being presented is to investigate the thermal performance of indirect, multi-tray solar drying system. Expressions for exergy in, exergy out and exergy loss for flat plate solar collector, drying chamber and trays kept in drying chamber were written under steady state conditions. Experiments were performed for 6 to 8 hours on two days namely 14/03/2014 and 24/03/2014 and the observations taken on 24/03/14 has been analyzed using Energetic and Exegetic approach. The value of first law efficiency for flat plate solar collector and solar dryer varied between 10% to 30.49% and 4.009% to 9.45% respectively. Second law efficiency of solar collector and solar dryer have been found varying from 0.7126% to 1.829%.and 49.85% to 67.75% respectively. The Exergetic efficiency for tray 1, tray 2 and tray 3 has been computed and these values varied from 90.43% to 93.412%, 72.684% to 92.352% and 78.179% to 94.61% for each trays respectively. Considering heavy energy and exergy losses from flat plate solar collector and drying chamber, the results of first Law and second Law efficiencies are in fair agreement with each other. ©, Copyright Association of Energy Engineers (AEE).